Sulcal pattern variation in extant human endocasts - (:unkn) unknown (My University, 2018)
abstract de congrès publié : De Jager EJ, Van Schoor AN, Hoffman JW, Oettle AC, Fonta C, Beaudet A. 2018 Sulcal pattern variation in extant human brain endocasts. American Association for Physical Anthropologists. Austin, April 10-14. American Journal of Physical Anthropology, 165, suppl 63 (poster).
Keywords: African Research